Revolutionizing recruitment: the synergy of artificial intelligence and human resources - Iyer, Vishwanathan (Review of Artificial Intelligence in Education, 2023)
Objective: To critically assess the impact of Artificial Intelligence (AI) on the recruitment process within the Human Resources (HR) sector, pinpointing its potentialities and challenges. Method: A comparative approach was employed to contrast traditional recruitment strategies with AI-enhanced techniques. The analysis centered on the inherent advantages and challenges of AI adoption in recruitment. Results: The benefits of AI in recruitment significantly outweigh its limitations. The research indicates a trend of broad endorsement of AI in the corporate realm, with AI systems adeptly: a) cataloging behavioral patterns, b) determining job fit based on disposition, c) synchronizing these with job specifications, d) interfacing with enterprises, e) facilitating virtual interviews, and f) engendering synergistic outcomes. Conclusions: AI, reflecting its foundational ethos, holds the potential to produce both commendable and adverse effects in recruitment. The self-evolving capability of AI necessitates continuous oversight to circumvent governance challenges. Practical Implications: Responsible adoption of AI in HR can optimize recruitment processes, rendering them more efficient and precise. However, it is imperative to strike a harmonious balance between artificial and human intelligence to ensure ethical and efficacious deployment, minimizing risks and maximizing benefits.